Ediacaran-Cambrian paleosols of Nevada and California - Gregory J. Retallack (PLoS ONE, 2025)
The Cambrian and Ediacaran sequence of California and Nevada is rife with unconformities, paleovalleys, paleosols, and fluvial facies. This study confirms shallow marine environments for grey stromatolitic dolostone and shale of northern localities (Mt Dunfee and Westgard Pass), but fluvial red sandstones and siltstone of southern localities (Johnnie, Eagle Peak, Emigrant Pass, Donna Loy, and Cadiz) include paleosols as evidence for coastal plain and fluvial environments. Three marine transgressions into the southern localities, were in Ediacaran Johnnie Formation, earliest Cambrian Manykodes pedum zone, and Early Cambrian Olenellus trilobite zone. The southern locations have paleosols with Ediacaran fossils Ernietta, Pteridinium, Swartpuntia, and Hallidaya in growth position, as evidence that these vendobiont fossils were non marine. The paleosols include aridland Gypsids and Calcids, as well as weakly developed soils, with diagnostic LYREE enrichment, and low boron content of paleosols. Northern Ediacaran marine rocks, in contrast, are limestones with Cloudina and Wyattia, and shales with Conotubus and Wutubus. Identical marine and non-marine facies and biotas are also known from Ediacaran and Cambrian rocks of Namibia. Ediacaran marine wormlike fossils (Wormworld) were ecologically distinct and geographically separated from non-marine, sessile, vendobionts (Mattressland).